2020
DOI: 10.3390/toxics8040120
|View full text |Cite
|
Sign up to set email alerts
|

Radon—The Element of Risk. The Impact of Radon Exposure on Human Health

Abstract: Lung cancer is a heterogeneous group of diseases with multifactorial aetiology. Smoking has been undeniably recognized as the main aetiological factor in lung cancer, but it should be emphasized that it is not the only factor. It is worth noting that a number of nonsmokers also develop this disease. Radon exposure is the second greatest risk factor for lung cancer among smokers—after smoking—and the first one for nonsmokers. The knowledge about this element amongst specialist oncologists and pulmonologists see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(20 citation statements)
references
References 101 publications
(117 reference statements)
0
20
0
Order By: Relevance
“…Chemical factors are considered to be an important cause of SBS. Some building materials, such as sand and gravel, contain radon associated with lung diseases and even cancer, 23 while some decorative materials contain chemical components that may induce SBS, such as formaldehyde and benzene. Many renovated houses had formaldehyde levels above guideline values, 24 which may increase the expression of adhesion molecules on human mucosal microvascular endothelial cells (HMMECs), irritating the nasal mucosa, eyes, and respiratory tract 25 .…”
Section: Discussionmentioning
confidence: 99%
“…Chemical factors are considered to be an important cause of SBS. Some building materials, such as sand and gravel, contain radon associated with lung diseases and even cancer, 23 while some decorative materials contain chemical components that may induce SBS, such as formaldehyde and benzene. Many renovated houses had formaldehyde levels above guideline values, 24 which may increase the expression of adhesion molecules on human mucosal microvascular endothelial cells (HMMECs), irritating the nasal mucosa, eyes, and respiratory tract 25 .…”
Section: Discussionmentioning
confidence: 99%
“…In reality, sometimes large differences within the same region or in two adjoining buildings can be observed. Experimental results attest that Radon distribution is presented as a discrete case, hence the need to carry out measurements in each building [38].…”
Section: Introductionmentioning
confidence: 87%
“…Research has shown the compound of radon, among others with p53 mutations, increased expression of the KRAS oncogene and down-regulation let-7 microRNA. A slightly increased frequency of ALK gene rearrangements has also been reported in patients exposed to radon [ 8 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 91%
“…Apart from that, there is a regulation concerning the content of radium (Ra-226) in building materials, which is a direct predecessor of gaseous radon Rn-222. Additionally, there are individual possibilities of reducing the exposure to this element, mainly through an appropriate ventilation of houses [ 14 , 15 , 16 ]. Radon is therefore another environmental risk factor for lung cancer, and its concentration in the vicinity of humans can be modified by appropriate behavior or lifestyle.…”
Section: Introductionmentioning
confidence: 99%